A deep-learning technique for phase identification in multiphase inorganic compounds using synthetic XRD powder patterns - Jin-Woong Lee; Woon Bae Park; Jin Hee Lee; Satendra Pal Singh; Kee-Sun Sohn (Nature Communications, 2020)
Identifying the composition of multiphase inorganic compounds from XRD patterns is challenging. Here the authors use a convolutional neural network to identify phases in unknown multiphase mixed inorganic powder samples with an accuracy of nearly 90%.